Two-Step, One-Pot Pyrrole Synthesis by Iron-Catalyzed Carboamination/Copper-Mediated Cyclization - Murphy, Grace K.; Richards, Corey A.; Applegate, Seth A.; Neely, Jamie M. (Synlett, 2022)
Herein we report a method for pyrrole synthesis via iron-catalyzed carboamination/copper-mediated cyclization that is completely regioselective for the formation of 1,2,4-trisubstituted products. This two-step, one-pot process offers significant improvements to previously reported conditions including the use of a readily available copper(I) source and a markedly less arduous experimental procedure. Exploration of the substrate scope reveals a variety of arylacetylenes undergo pyrrole formation to afford single isomer products. Isotopic labelling data points to a mechanism involving activation of the alkyne moiety by the copper(I) reagent during the cyclization step.
Keywords: iron; copper; pyrroles; cyclization; regioselectivity